A constituição do ethos do idoso no Facebook: argumentação e retórica - Costa, Sílvia Scola da (2017)
This thesis, inserted in the research line Reading, Writing and Teaching of Portuguese Language, of the Program of Postgraduate Studies in Portuguese Language of the Pontifical Catholic University of São Paulo, has as its theme the study of the construction of the ethos of the elderly in the relationship Social page: Facebook. When placing himself in the digital social network, the clerk assumed the authorship of what he writes: if he writes of himself, if he uses multimodality for such, he is an author and a character. Networking does not have to be a "truth," but it needs to be believable and, in that sense, persuasive. Language, on the other hand, translating man and revelation, objectively or in a less explicit way, the character of being ascertained by the unveiling of the rhetorical devices used does not reveal itself. To make this possible, we collected thirty-six senior profiles on the page and analyzed the rhetorical manifestation of character-building traits in line with Aristotle's studies of the passions and character manifested by young, old, and elderly of his time. We also collected twenty youth profiles and twenty adult profiles so that we could carry out a comparative analysis and understand whether the discursive form of character manifestation that Aristotle preached more than two thousand years ago remains, to a lesser or greater degree, in the Virtual reality experienced nowadays, for digital natives, as by digital immigrants. With the aid of modern studies of rhetoric, we understand that in verbal interaction through Facebook, ethos, pathos, and logos, they intermingle for a single discursive purpose: to attain an adherence of the other, at least by deliberation or by simple delight. In this way, the rhetorical act is filled with very idiosyncratic action, without, however, hiding the impulsive and thematic postures of a generation. An analysis has revealed expressive manifestations about a posting of euphoric passions and traits of character still remaining in contemporary society or in the choice of the themes in question, in a rhetorical discourse very expressive and revealing a way to be an elder in contemporary society